Predicting visual outcome following retinectomy for retinal detachment. Issue 7 (12th June 2008) - de Silva, D J; Kwan, A; Bunce, C; Bainbridge, J
Abstract : Aim: To evaluate outcome following retinectomy surgery and to identify factors that predict visual outcome. Methods: This was a retrospective uncontrolled interventional case-series of patients who underwent retinectomy surgery at Moorfields Eye Hospital (London, UK) during a 2-year period. We recorded peri-operative factors with the potential to influence functional outcome including aetiology of retinal detachment; type of ocular trauma; preoperative visual acuity and intraocular pressure; grade of PVR; extent and position of retinectomy; peri-operative complications; tamponade agent and prophylactic 360° laser retinopexy. Results: The authors identified 145 patients who underwent retinectomy surgery. After a mean follow-up period of 23.2 months (6–58 months) 16% of eyes had visual acuity of 20/60 or better, 33% had visual acuity of between 20/60 and 20/400, and 51% had visual acuity less than 20/400. Visual acuity was improved or stable in 76% of eyes and the rate of complete retinal reattachment was 68%. For each stepwise increase in the grade of PVR there was an approximately 15% increased risk of final visual acuity of less than 20/40. The use of additional 360 degree prophylactic laser retinopexy prior to removal of silicone oil was associated with a higher rate of final retinal reattachment. Conclusions: This study provides important information to help surgeons inform and counsel their patients about visual prognosis following retinectomy surgery. Furthermore, the study demonstrates that the aetiology of retinal detachment, the stage of PVR and the use of 360° laser retinopexy have significant predictive value for visual outcome. Summary: Retinectomy is a valuable technique in the management of complex retinal detachment but is associated with a significant risk of retinal redetachment and poor visual outcome. In this large study, we identified that the aetiology of retinal detachment, the stage of proliferative vitreoretinopathy and the use of 360° prophylactic laser retinopexy are predictive of functional outcome.